Sono-chemical synthesis of ZnO nano-particles and their application in hydrogen sulphide gas sensing - Khanna, P. K.; Kate, Kunal; Dhanabalan, K.; Banerjee, Shaibal; Reji, Nedunnkandathil; Shinde, S. D.; Jain, G. H. (Journal of Nanoscience and Nanotechnology, 2012)
Herein we describe synthesis of ZnO nanoparticles by using alkaline solution of ZnX2 (X = NO3, Cl) under ultrasound energy of 20 KHz. The reaction can be completed in about 1-2 hours. As prepared powders were analyzed by XRD measurement to find that the product is hexagonal phase pure ZnO. UV-Visible measurement of aq. solution showed absorption band at similar to 365 nm and photoluminescence (PL) indicated multiple bands in visible region due to deep traps owing to high temperature sintering. The hydrophilicity can be imparted by use of a suitable polyelectrolyte. Freshly prepared samples showed good dispersion in aqueous and alcoholic medium. The thick films derived from the ZnO nano-particles showed excellent sensing for hydrogen sulphide gas.
Keywords: Gas-Sensing; Sono-Chemical; synthesis; ZnO Nano-Particles

Studies on CL-20/HMX (2:1) cocrystal: a new preparation method and structural and thermokinetic analysis - Ghosh, Mrinal; Sikder, Arun K.; Banerjee, Shaibal; Gonnade, Rajesh G. (Crystal Growth & Design, 2018)
A new preparation method for CL-20/HMX (2:1) cocrystal has been established at the laboratory level that is amenable for scale up. Solvent evaporation from a saturated solution of the stoichiometric mixture in the presence of a high boiling antisolvent, comparatively a very efficient and cheaper method, yielded pure cocrystals. Cocrystals were well characterized by spectroscopic, thermoanalytical tools, X-ray diffraction, and microscopic techniques. A correlation of percentage of cocrystal formation with evaporation rate has been obtained through quantitative analysis using Raman spectrometry. An evaporation rate of <1 mL/min consistently produced pure cocrystal confirmed by Raman and powder X-ray diffraction analysis. Thermokinetic analysis suggests the cocrystal to be more stable than CL-20 with an energy of activation of 65 kcal/mol, higher than CL-20 but inferior to HMX. Significant augmentation in the values of k and A over CL-20 justified a faster decomposition rate. Enhanced insensitivity toward friction and impact forces and higher measured velocity of detonation indicate improved performance on incorporation into high explosive formulations.